Research Progress on Simulation of Tritium Permeation Behaviors in Stainless Steel - Shi-ping WEI; Yuan HU (He huaxue yu fangshe huaxue)
Fusion energy is a kind of clean energy with very low pollution for large-scale production, and the current mainstream solution is magnetic confinement nuclear fusion, which is considered to be the most promising way to achieve commercial fusion power generation. Radioactive tritium, as one of the fuels of fusion reactors, is easily permeable in stainless steel structural material, which causes a huge waste of scarce fuel and also brings huge cost to radiation protection. It is important to study the tritium permeation behaviors in stainless steel for the tritium self-sufficiency and safe operation of fusion reactor. They are closely related to the structural safety of fusion reactor components, tritium extraction of blankets, fuel cycle of tritium plant as well as the protection of the public and environment. This paper introduces the mechanism of tritium permeation in stainless steel and main methods and research progress of tritium penetration behavior simulation both domestically and internationally, analyzes the existing problems in the simulation of tritium permeation behaviors, and looks forward to the new research direction. High-temperature gas phase permeation(GDP), thermal desorption spectrum(TDS) and chemical etching methods are generally used to study the adsorption, dissociation, diffusion and desorption of hydrogen isotopes in stainless steel from the experimental aspect. It is pointed out that there are few experimental studies on direct use of tritium, which leads to the great uncertainty of the corresponding tritium permeation data. At present, the experimental research mainly focuses on the tritium permeability parameters of stainless steel and the degree of related influence factors, but no systematic theoretical system has been formed. The tritium permeation behaviors in stainless steel under the radiation of fusion neutron also need to be further studied, and explain the effects of radiation damage, surface stress, defects, dislocations, and impurity elements on tritium adsorption, tritium diffusion, tritium retention, and tritium desorption. The classical tritium permeation model and a single simulation method cannot accurately describe the tritium permeation behaviors. There are still many unsolved problems and even disputes about the theoretical models. The single tritium permeation simulation approach has specific disadvantages. An organic combination of existing tritium permeation simulation methods such as empirical formula solution, system dynamics(SD) simulation, computational fluid dynamics(CFD) simulation and first principles calculation is proposed to achieve multi-scale from zero dimension to three dimension and multi-physical coupling accurate simulation. This work will provide valuable theoretical guidance and technical solutions for accurate tritium transport simulation in stainless steel.